Intellectual capital and value creation: evidence from the Portuguese tourism industry - Costa, Vânia (2022)
The intellectual capital is an important corporate asset, able to generate sustainable competitive advantages and higher financial income. In the literature is recognized as a key element of the value creation in contemporary economy. One of the factors that emphasized the importance of intellectual capital in an organization was to change the focus of tangible capital management for the intangible, as a result of the affirmation of its importance in the process of creating organizational value (Abeysekera, 2006). This work aims to evaluate and compare the intellectual capital in its three dimensions: (i) human capital, (ii) structural capital and (iii) relational capital, to identify the added value and the efficiency of each dimension in the context of the tourism sector. To approach the aim of the study the method Value Added Intellectual Coefficient (VAIC™) was applied and the practical data were collected from the Simplified Business Information (IES) through SABI (Iberian Balance Sheet Analysis System) database. Therefore, the economic and financial information was collected from balance sheets and financial reports of 46 951 Portuguese companies in the tourism sector, during the 2007 to 2016 period. The results showed that all the dimensions of the intellectual capital has a positive and significant impact on the business performance of the tourism sector. Therefore the results coincide with the literature, since human capital is the most effective dimension of intellectual capital and value creation (average representation of 60%), suggesting that the substantially more efficient intellectual capital than the financial component. However, between 2007 and 2016 we concluded a VAIC decrease of 12.7% (3.47 in 2007 and 3.03 in 2016), reflecting a decrease in the efficiency of capital employed (-10%), human capital (- 21%) and relational capital (-19%). Analysing the data taking into account the reference values concerning indices of efficiency we can conclude that the indexes present good and excellent performance during the period under review, reflecting a minimum corporate income for efficient business income. The application of the VAIC™ model provides practical implications for management and valorization of intellectual capital. So the empirical results with the present analysis are of relevance for future strategy for the tourism sector development in Portugal.